Combination antifungal therapy for cryptococcal meningitis. Issue 607 (May 1976) - Tobias, J. S.; Wrigley, P. F. M.; Shaw, Elizabeth
Abstract : Two patients with Hodgkin's disease and cryptococcal meningitis are described. Both patients were treated with a combination of the two antifungal agents, amphotericin B and flucytosine. Nephrotoxicity was easily reversible in both patients and clinical improvement was seen with this combination therapy. Intrathecal therapy with amphotericin B was used in both patients. The optimal treatment of this disease may prove to be a combination of oral flucytosine, with amphotericin B given by intrathecal injection as well as rapid low dose intravenous injection.